Evaluasi Penerimaan Peserta Didik Baru Sistem Zonasi. - Ibrahim; Setyaningsih, Kris; Nursa’diah, Destina (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
This study aims to analyze how the evaluation of new student admissions through the zoning system is conducted at SMP Negeri 2 Sembawa Banyuasin. The researcher employs a descriptive qualitative approach, using qualitative research methods. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, verification, and conclusion. To ensure data validity, the study uses source triangulation and technique triangulation. The research findings indicate that the evaluation of new student admissions through the zoning system at SMP Negeri 2 Sembawa Banyuasin has been well-implemented. The evaluation shows indicators such as transparency, openness, fairness, and equity. The evaluation of new student admissions through the zoning system has been carried out effectively, adhering to the zoning admission process by ensuring transparency, openness, fairness, and equity for all members of the community wishing to enroll their children at SMP N 2 Sembawa